DEVELOPMENT OF LATERITE ORE PROCESSING AND ITS APPLICATIONS - Fathan Bahfie; Azwar Manaf; Widi Astuti; Fajar Nurjaman; Erik Prastyo; Ulin Herlina (Puslitbang tekMIRA, 2022)
Nickel ore is found in two types sulfide and laterite. The sulfide is a nickel ore that has high nickel content and low reserves of natural resources than of the zinc laterite. In contrast, the laterite is a rock mineral that contains the iron-nickel oxide compounds. There are two methods of processing nickel laterite, namely hydrometallurgy and pyrometallurgy. The former is a method that uses leaching by a chemical solution or solid such as acid, as a reducing agent. The alkaline leaching (ammonia) is the most optimal method to obtain a nickel grade with the highest recovery but it needs more modification. Pyrometallurgical method uses high heat up to 1800°C, so it requires a lot of energy and needs improvement to decrease the carbon usage. The rotary kiln-electric furnace method is the optimal method for developing the nickel laterite. These methods generate products that can be applied to various fields. For example, the pyrometallurgy method produces nickel pig iron and ferronickel as raw materials for stainless steel and steel alloys. The hydrometallurgy method produces nickel sulfate and nickel oxide with a purity of 99% by weight as raw materials for magnets, sensors, and batteries. Hence, the hydrometallurgy method still needs improvements for the environmentally friendly reagent. Therefore, bioleaching will be a nickel laterite leaching process in the future by using bacteria as the reducing agent.